Pemanfaatan Aplikasi Google Drive Sebagai Media Pembelajaran di Kalangan Mahasiswa - Rifdah, Rifdah; Hindun, Hindun (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2024)
The internet is a global network that is often used by millions of people to provide information, communication, and broad digital access. The existence of this internet makes a great opportunity for its use to develop technological skills. One of the learning media used by students is Google Drive. Google Drive is a place to store data that has a large capacity, 15 GB (Gigabyte). The use of Google Drive can be accessed anywhere and anytime. Google Drive has many features, such as Gmail, Google Documents, Google Plus, and so on. The use of this application has a very important role for education because it makes it easier for users to find valid sources and can store all kinds of file data. It cannot be denied that the existence of technology like this makes one's learning ability increase, because it is easy to find material to be studied and also increases the effectiveness of learning. This type of research was conducted by filling out questionnaires to students. The results showed that the utilization of using Google Drive, students can operate their learning experience, can create a collaboration, and can manage their tasks in an efficient way.